Stealing Thunder in Negative Political Advertising: The Persuasive Impact of One-sided and Two-sided Negative Messages on Partisan Individuals. (March 2020) - Kim, Kenneth
Although two-sided persuasion is a common technique in political speeches, few research has reported the relative persuasiveness of a one-versus two-sided message in the context of negative political advertising. Participants ( N = 116) viewed a negative political ad, varying in message sidedness (one-sided vs. two-sided) and partisan match (partisan-match vs. partisan-mismatch vs. unaffiliated). Multivariate results revealed the relative advantage of two-sided persuasion in the partisan-match condition where participants viewed a negative ad targeting their supporting party candidate. One-sided persuasion was more effective in the partisan-mismatch condition where participants viewed a negative ad criticizing the opposition party candidate. Implications for the practice of strategic negative political campaigns were discussed.